2010
DOI: 10.1128/mcb.01124-09
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase POLN Participates in Cross-Link Repair and Homologous Recombination

Abstract: All cells rely on DNA polymerases to duplicate their genetic material and to repair or bypass DNA lesions. In humans, 16 polymerases have been identified, and each bears specific functions in genome maintenance. We identified here the recently discovered polymerase POLN to be involved in repair of DNA cross-links. Such DNA lesions are highly toxic and are believed to be repaired by the sequential activity of nucleotide excision repair, translesion synthesis, and homologous recombination mechanisms. By function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 43 publications
5
106
1
1
Order By: Relevance
“…Functional Assays-Clonogenic assays were perfomed as previously described (39). Two rounds of siRNA were performed, 24 h apart.…”
Section: Methodsmentioning
confidence: 99%
“…Functional Assays-Clonogenic assays were perfomed as previously described (39). Two rounds of siRNA were performed, 24 h apart.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular cloning of p125 showed that the catalytic core was highly conserved in evolution from T4 bacteriophage to human Hao et al, 1992;Yang et al, 1992], and Pol d is now classified as a member of the B family polymerases. Closely allied with the early history of Pol d are studies of the eukaryotic DNA-sliding clamp, proliferating cell nuclear antigen (PCNA; [Kuriyan and O'Donnell, 1993;Moldovan et al, 2010]), which was discovered as a processivity factor that stimulated Pol d activity [Prelich et al, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…DSBs can be repaired by nonhomologous end-joining (NHEJ) or homologous recombination (HR). The DNA polymerases Pol e, Pol b, Pol f, Pol h, Pol y, Pol k, Pol l function in DSB repair by HR or NHEJ [Holbeck et al, 1993;Jessberger et al, 1993;Wang et al, 2004;Xu et al, 2005;Zan et al, 2005;Rattray and Strathern, 2005;Masuda et al, 2006;Nick McElhinny, 2008;Kidane et al, 2010;Moldovan et al, 2010]. The pathways of homologous recombination and nonhomologous end-joining have been reviewed in Chaudhuri and Alt [2004] and San Filippo et al [2008].…”
Section: Dna Repair and Recombinationmentioning
confidence: 99%